Assessment of acidity and the zeolite porous structure on hydrocracking of HDPE. Issue 15 (4th July 2022) - Costa, Cátia S.; Dao Thi, Hang; Van Geem, Kevin M.; Rosário Ribeiro, M.; Silva, João M.
Abstract : Rationale for catalytic activity and product distribution in HDPE hydrocracking promoted by zeolite catalysts. Assessment of catalyst stability. Abstract : Plastic waste (PW) management poses a great challenge that must be urgently addressed. Chemical recycling (CR) will be undoubtedly needed to attain a low carbon, resource efficient and sustainable economy. In contrast to pyrolysis, hydrocracking (HDC) converts PW into a mixture of hydrocarbons with a low olefin, aromatic and naphthene content. Nevertheless, the selection of a suitable catalyst is extremely important for the efficiency of this process. In the present work, a set of zeolite structures (H-USY, H-ZSM-5, H-MOR and H-FER) were applied as catalytic systems for the HDC of HDPE in a batch autoclave reactor, and the effect of the acidity and of the porous structure on the process conversion and product distribution was evaluated. The stability of the zeolites was also assessed during this work. The results show that H-ZSM-5 is the best catalyst to convert HDPE into valuable HDC fractions followed by H-MOR ≥ H-USY ≥ H-FER, depending their catalytic performance with respect to their structural, textural and acid properties. H-ZSM-5 also has the highest tendency to form lighter hydrocarbons in the C3 –C5 range. Regarding stability, coking tendency, and robustness, H-USY and H-ZSM-5 almost completely recover their initial activity upon regeneration, implying that they can be easily used for at least two HDC cycles.